INOVASI PELAYANAN PUBLIK “MENCARI KEKASIHKU” DI DISPENDUKCAPIL KABUPATEN GROBOGAN - Safitri, Aprilia Dewi; ., Maesaroh; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Innovation of “Mencari Kekasihku” is an innovation at the Population and Civil Registration Office of Grobogan Regency aimed at improving the validity of population data on changes in marital status among muslim residents in Grobogan Regency. This study aims to identify and analyze the characteristics of the public service innovation “Mencari Kekasihku” at the Population and Civil Registration Office of Grobogan Regency, as well as identify the supporting and inhibiting factors of the public service innovation “Mencari Kekasihku